Assessing Arctica islandica as a proxy for Scottish marine climate change - Stott, Keziah J. (University of St Andrews, 2014)
This thesis investigates the potential of the bivalve Arctica islandica (Linnaeus, 1767) from fjordic sites in NW Scotland for reconstructing past marine environmental /climatic variability. Using dendrochronological and sclerochronological techniques, six master chronologies were created which when compared show little common variability between the sites, indicating no common response to regional scale forcing. The chronologies were compared to local and regional scale SST and land based datasets, with no significant, time stable responses to climate found. It is clear the growth/climate response of A. islandica from these sites is complex, potentially due to the shallow nature of the sample sites, direct local drivers such as food availability and, potentially, anthropogenic activity in the region. Geochemical analyses of the shell material were undertaken to examine the timing and magnitude of the radiocarbon bomb-peak and the stable carbon isotope signature of the oceanic Suess Effect. The timing of the radiocarbon bomb-peak in Loch Etive does not appear to match previously published results from other marine locations and are a potentially serious challenge to the assumption that A. islandica GI are always annual features. Results comparing δ¹³C values and the age of the specimen when these values are incorporated into the shell material strongly indicate an ontogenetic control over δ¹³C, meaning the Suess Effect could not be effectively investigated. To take these ontogenetic influences into account it is suggested that any data from the juvenile period of shell life is not used. Analysis of shell biometrics and morphology indicate significant relationships between shell age and height and age and weight, however the errors for these are large (±78 years and ±80 years respectively). These results indicate that despite large errors shell height, as a predictor of age, has the potential to be used for in situ population studies. "Funding for the NERC SCUBA diving was undertaken under the NERC grant No: ...